If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + 4m + -28 = 45 Reorder the terms: -28 + 5m + 4m = 45 Combine like terms: 5m + 4m = 9m -28 + 9m = 45 Solving -28 + 9m = 45 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '28' to each side of the equation. -28 + 28 + 9m = 45 + 28 Combine like terms: -28 + 28 = 0 0 + 9m = 45 + 28 9m = 45 + 28 Combine like terms: 45 + 28 = 73 9m = 73 Divide each side by '9'. m = 8.111111111 Simplifying m = 8.111111111
| 24-4x=15x | | b-36.9=5.1b | | 3m+1=4-6 | | -16(-19+11r)-18= | | -(6+5r)=-6-5r | | 635-35= | | (9n+1)-(6n+(-2))= | | d-182=-5d-8 | | (-3n+1)-(-5n+8)= | | A=x^2-3x+2 | | 5x+4(9x+4)=32 | | -20p+16=-9p-18-13p | | 3x^7+3x-15=0 | | 9-ln(5-x)=0 | | x^2-8x+16=-2 | | 6+2p-4=7p+11-4p | | -2x-14=6 | | 9+11a=-5a+12 | | (3n+1)-(5n+(-7))= | | n+137=-2n-4 | | 4d-5=0 | | 4y+(y+35)=180 | | p(x)=(x-(2-3i))(x-(2+3i)) | | 0=12x^2-40x-32 | | (-7n+(-3))-(-9n+5)= | | 18m-14=18m+18+2m | | -6+4=14y-10-13y | | 25/5(2+3)=25 | | 8n-9=n+285 | | (-9n+4)-(-2n+(-5))= | | 2abs(x-15)+abs(15-x)=27 | | 25/5(2+3)=1 |